2012
DOI: 10.5324/nje.v22i2.1555
|View full text |Cite
|
Sign up to set email alerts
|

Successfully aging elderly (SAE): A short overview of some important aspects of successful aging

Abstract: Whether one falls into the category of successfully aging elderly (SAE) is generally determined by biological, medical, psychological, and cognitive factors. SAE, pathological aging and usual aging, are the three subgroups presented in the seminal science paper by Rowe & Kahn in 1987. SAE is currently vaguely defined as being free of disease, having preserved cognitive function and an active life, but a more detailed definition is lacking. As a result, the research on SAE is heterogeneous and hard to summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For example, it is not necessary for every person to get sick, but it is almost certain that they will have their immune system influenced sometime during their lifetime. Thus, as it was mentioned above the disease absence as risk factor, Stordal et al make clear the fact that it is not only linked to mental or physical disease but also with the whenever existing risk factor for the respective disease [ 30 ]. Yet, Franzon et al with a prospective study in Sweden, considering the relations among some modifiable factors, such as that of middle age, aging and physical or mental function in relation to the survival at a very old age, showed that a normal BMI during the middle age and the abstention from smoking, related to successful aging and longevity, setting smoking and bodily weight in the crucial risk factors [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is not necessary for every person to get sick, but it is almost certain that they will have their immune system influenced sometime during their lifetime. Thus, as it was mentioned above the disease absence as risk factor, Stordal et al make clear the fact that it is not only linked to mental or physical disease but also with the whenever existing risk factor for the respective disease [ 30 ]. Yet, Franzon et al with a prospective study in Sweden, considering the relations among some modifiable factors, such as that of middle age, aging and physical or mental function in relation to the survival at a very old age, showed that a normal BMI during the middle age and the abstention from smoking, related to successful aging and longevity, setting smoking and bodily weight in the crucial risk factors [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, healthy aging can in fact be described as either successful or usual/common [152,153]. Successful aging, also called optimal health or super-aging [184], is associated with a low probability of disease or disability, high cognitive and physical function, and active engagement in social activities, while usual/common aging describes good cognitive and physical performance levels but higher risks of disease or disability [152]. Even if the theoretical concept of successful aging has been questioned because of the difficulty to find a consensual definition and implementation [36,120], it offers a more positive prospect on aging and has opened a line of research focusing on the biological and lifestyle factors that may favor a more performant aging [10,200].…”
Section: Universal Vs Idiosyncratic Agingmentioning
confidence: 99%
“…However, considering that "individual and collective phobias about the very process of growing older" remain highly visible in contemporary societies, the model has been criticized for failing to completely "erase the stereotypical representations of old age" [14]. Although there have been numerous empirical applications of the successful aging perspective [15], there is no consensus about its definition and, consequently, operationalization [1,16,17]. The concept of successful aging remains in a state of flux, with new research studies proposing different domains and/or operational definitions.…”
mentioning
confidence: 99%